Advancing grid modernization and smart grid policy: a discussion paper - Unidentified author; Center for the New Energy Economy, publisher (Colorado State University. Libraries, 2013)
This paper is a result of the Advanced Energy Economy (AEE) Grid Modernization Policy Forum on June 18th, 2013 in Boulder, Colorado. The purpose of the forum was to identify the advanced energy industry's state policy priorities for smart grid utilization and deployment. The intended audience for this paper is state regulators, legislators, governor's' offices and other policy makers. This paper is not intended to be a comprehensive report on the smart grid. Rather, it is a summary of the most relevant barriers to broader smart grid adoption and corresponding policy options put forth for consideration by legislators, regulators and industry participants.
Keywords: Energy policy; Renewable energy sources -- Law and legislation -- United States; Smart power grids